PENGARUH KOMPENSASI, DISIPLIN KERJA, DAN MOTIVASI TERHADAP PRODUKTIVITAS KARYAWAN BANK SYARIAH INDONESIA: (Studi pada Bank Syariah Indonesia Kec. Kabanjahe) - Ayu Febriyana Tanjung; Ainun Mardhiyah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
The success of the company is determined by human resources so that companies need to meet the needs of employees so that employees can work productively. Employee productivity is the ability of employees to complete tasks effectively and efficiently. Employee productivity can be influenced by several factors including compensation, work discipline, and motivation. The purpose of this study was to determine how the effect of compensation, work discipline, and motivation on employee productivity at Bank Syariah Indonesia Kabanjahe District. This study uses quantitative research methods with an associative approach. The population in this study were employees of Bank Syariah Indonesia in Kabanjahe District with 35 respondents. Data collection was carried out through distributing questionnaires using the Likert scale data measurement method. Multiple linear regression analysis methods and hypothesis testing using SPSS. The results showed that Compensation has a significant positive effect on Employee Productivity. Work Discipline variable has no effect on Employee Productivity. Work motivation variable has a significant positive effect on employee productivity. Compensation, work discipline and motivation variables simultaneously have a positive and significant effect on employee productivity. The Rsquare value obtained is 0.281. This means that 71.9% is influenced by other variables not included in this study.